2019
DOI: 10.1126/science.aav5282
|View full text |Cite
|
Sign up to set email alerts
|

Ultrapotent chemogenetics for research and potential clinical applications

Abstract: Improved agonists for chemogenetics Targeting ligand-responsive receptors to specific groups of cells, a strategy known as chemogenetics, is a powerful tool in many neurological applications. There is increasing interest in extending these tools for human treatment. Magnus et al. designed chemogenetic ion channels that improve currently available systems and are activated by the clinically used antismoking drug varenicline. They engineered a ligand-binding domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(150 citation statements)
references
References 75 publications
5
102
1
Order By: Relevance
“…Only iDianiSnFR, which lacks His68, binds varenicline with EC 50 > 10 μM. Even tighter binding has been achieved with varenicline derivatives at mutated ligand-gated channels ( Magnus et al, 2019 ). On the one hand, the cellular experiments described here cannot use iDrugSnFR pairs with dissociation rate constants less than ~0.1 s –1 , corresponding to an EC 50 of less than ~100 nM.…”
Section: Discussionmentioning
confidence: 99%
“…Only iDianiSnFR, which lacks His68, binds varenicline with EC 50 > 10 μM. Even tighter binding has been achieved with varenicline derivatives at mutated ligand-gated channels ( Magnus et al, 2019 ). On the one hand, the cellular experiments described here cannot use iDrugSnFR pairs with dissociation rate constants less than ~0.1 s –1 , corresponding to an EC 50 of less than ~100 nM.…”
Section: Discussionmentioning
confidence: 99%
“…Only iDianiSnFR, which lacks His68, binds varenicline with EC50 > 10 μM. Even tighter binding has been achieved with varenicline derivatives at mutated ligand-gated channels (Magnus, et al, 2019). On the one hand, the cellular experiments described here cannot use iDrugSnFR pairs with dissociation rate constants less than ~ 0.1 s -1 , corresponding to an EC50 of less than ~ 100 nM.…”
Section: The Idrugsnfr Paradigmmentioning
confidence: 86%
“…Genetic tools have made a dramatic contribution to a better understanding of the nervous system. Thus human genetic studies have identified causative mutations for a variety of disorders 29 , whilst gene and cell silencing 30 and in particular activity-based reporter systems such as CANE have proved extraordinarily informative 31 .…”
Section: Discussionmentioning
confidence: 99%